A numerical simulation of viscous shear effects on porous squeeze-film using the Darcy-Brinkman model - Nabhani, Mohamed; El Khlifi, Mohamed; Bou-Said, Benyebka (Mechanics & industry : an international journal on mechanical sciences and engineering applications, 2010)
In recent decades, problems related to the squeeze of fluid films in the presence of a porous medium draw attention of researchers and are the subject of many applied studies for industry and biomechanics. Our concerns in this paper are the numerical simulation of the viscous shear stresses effects on the fluid film characteristics between two discs with one porous. This study is based on the coupling, at the fluid film-porous disc interface, of the Darcy-Brinkman equations in the porous medium and the modified Reynolds equation describing the flow in the fluid film. The system of equations obtained is discretized by the means of finite differences method and solved numerically using the technique of Successive Over-Relaxation (SOR). The results show that the viscous shear effects increase the radial and the axial fluid film velocities as well as the squeeze film velocity but decrease the response time. Moreover, these effects are enlarged for smaller viscous shear parameter and for smaller fluid film thickness.